How Digital Literacy Can Drive Inclusive Progress Towards the 2030 SDGs - Senja Shafira, Vera; Ramadhani, Gina; Rachman, Ichsan Fauzi (Advances in Economics & Financial Studies, 2024)
This research examines the implications of increasing digital literacy for achieving the 2030 Sustainable Development Goals (SDGs), with a focus on the perspective of accessibility and inclusivity. Digital literacy, which includes an individual's ability to access, understand and use digital technologies effectively, plays a critical role in driving sustainable social, economic and environmental development. This research finds that increasing digital literacy can accelerate the achievement of various SDG goals, such as quality education (SDG 4), poverty alleviation (SDG 1), and reducing inequality (SDG 10). However, this research also identified significant challenges regarding accessibility and inclusivity, especially among vulnerable groups such as rural communities, people with disabilities, and minority groups. In conclusion, to maximize the benefits of digital literacy in achieving the SDGs, comprehensive and inclusive policies are needed that ensure equitable access to digital technology and relevant educational programs. This study provides strategic recommendations for policy makers and stakeholders in efforts to integrate digital literacy as a key component in development strategies sustainable.